Artificial Intelligence Identified Resilient and Vulnerable Female Rats After Traumatic Stress and Ethanol Exposure: Investigation of Neuropeptide Y Pathway Regulation - Denny, Ray R.; Connelly, Krista L.; Ghilotti, Marco G.; Meissler, Joseph J.; Yu, Daohai; Eisenstein, Toby K.; Unterwald, Ellen M. (Frontiers in Neuroscience, 2021)
Post-traumatic stress disorder (PTSD) is initiated by traumatic-stress exposure and manifests into a collection of symptoms including increased anxiety, sleep disturbances, enhanced response to triggers, and increased sympathetic nervous system arousal. PTSD is highly co-occurring with alcohol use disorder. Only some individuals experiencing traumatic stress develop PTSD and a subset of individuals with PTSD develop co-occurring alcohol use disorder. To investigate the basis of these individual responses to traumatic stress, single prolonged stress (SPS) a rodent model of traumatic stress was applied to young adult female rats. Individual responses to SPS were characterized by measuring anxiety-like behaviors with open field and elevated plus maze tests. Rats were then allowed to drink ethanol under an intermittent two bottle choice procedure for 8 weeks, and ethanol consumption was measured. An artificial intelligence algorithm was built to predict resilient and vulnerable individuals based on data from anxiety testing and ethanol consumption. This model was implemented in a second cohort of rats that underwent SPS without ethanol drinking to identify resilient and vulnerable individuals for further study. Analysis of neuropeptide Y (NPY) levels and expression of its receptors Y1R and Y2R mRNA in the central nucleus of the amygdala (CeA), basolateral amygdala (BLA), and bed nucleus stria terminalis (BNST) were performed. Results demonstrate that resilient rats had higher expression of Y2R mRNA in the CeA compared with vulnerable and control rats and had higher levels of NPY protein in the BNST compared to controls. The results of the study show that an artificial intelligence algorithm can identify individual differences in response to traumatic stress which can be used to predict subsequent ethanol drinking, and the NPY pathway is differentially altered following traumatic stress exposure in resilient and vulnerable populations. Understanding neurochemical alterations following traumatic-stress exposure is critical in developing prevention strategies for the vulnerable phenotype and will help further development of novel therapeutic approaches for individuals suffering from PTSD and at risk for alcohol use disorder.